Sequencing technique: an enhancement to 802.11 medium access control to improve the performance of wireless networks. (19th February 2008) - Krishna, P. Venkata; Iyengar, N.Ch.S.N.
This paper presents a technique known as sequencing on MAC layer for wireless networks. MAC layer issues are very important while accessing channel over wireless networks. Normally, communication uses Request To Send/Clear To Send (RTS/CTS) mechanism to access channel for transmission of data. Mostly, it is observed that RTS/CTS handshake may introduce some delay especially in case of wireless networks. Hence, a sequencing method is proposed where selected RTS packets are dropped based on a node sequence number to improve overall throughput of the network although individual performance of the transmission is reduced.